Small and Medium-Sized Enterprises in Global Markets: A Differential Approach for Services? - Lejárraga, Iza (OECD Publishing, 2014)
This study empirically investigates key restrictions to the internationalisation of small and medium-sized enterprises (SMEs) in manufacturing and across different types of services. The study explores the extent to which binding constraints faced by SMEs producing goods may differ from small firms operating in services sectors and takes stock of how existing policy initiatives address some of these differences. Our results suggest that while firm size clearly influences the trade performance of SMEs in manufacturing, it is an ambiguous predictor of export performance in the case of small-sized services firms. The findings show that firm size influences the choice of export channel and that small firms rely more on indirect and agglomeration networks. Finally, the results point to a strong degree of firm-level heterogeneity across services activities and enterprise size. It would seem that incorporating sectoral and size heterogeneity into existing policies might be desirable to address key constraints for SMEs
Keywords: Trade; Industry and Services